2005
DOI: 10.1038/sj.bjp.0706340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clopidogrel on the expression of inflammatory markers in rabbit ischemic coronary artery

Abstract: 1 Inflammation and platelet activation are critical phenomena in the setting of acute coronary syndromes. Platelets may contribute to increase ischemic injury by enhancing the inflammatory response of leukocytes and endothelial myocardial cells. Pharmacological inhibition of platelet activation prevents ischemic complications in patients with coronary diseases. Agents directed against the integrin glycoprotein IIb/IIIa (GP IIb/IIIa) receptor not only inhibit platelet aggregation but also have been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
3
40
1
Order By: Relevance
“…The present study showed that, in addition to its antiplatelet effects, clopidogrel showed anti-inflammatory activity; this was evidenced by the decreased serum levels of TNFα, ICAM-1, and RANTES, and heart tissue expression of TNFα, ICAM-1, IL-1β, and RANTES proteins. These findings were consistent with previous studies [22][23][24][25] and indicated that the cardioprotective effects of clopidogrel observed in the present study may be, in part, attributed to these anti-inflammatory effects.…”
Section: Wwwchinapharcom Zhang Y Et Alsupporting
confidence: 94%
“…The present study showed that, in addition to its antiplatelet effects, clopidogrel showed anti-inflammatory activity; this was evidenced by the decreased serum levels of TNFα, ICAM-1, and RANTES, and heart tissue expression of TNFα, ICAM-1, IL-1β, and RANTES proteins. These findings were consistent with previous studies [22][23][24][25] and indicated that the cardioprotective effects of clopidogrel observed in the present study may be, in part, attributed to these anti-inflammatory effects.…”
Section: Wwwchinapharcom Zhang Y Et Alsupporting
confidence: 94%
“…A study by Molero et al in an animal model of myocardial ischemia found that administration of clopidogrel produced anti-inflammatory effects in the ischemic coronary artery, reflected in reductions in expression of P-selectin, CD40L, and tissue factor. 38 Clopidogrel also was found in this study to protect the expression of endothelial nitric oxide synthase protein, which is downregulated under inflammatory conditions. A study by Pels et al in a porcine coronary injury model demonstrated that long-term administration of clopidogrel (3 months) significantly reduced the number of inflammatory CD3…”
supporting
confidence: 63%
“…Studies have shown that the protection from progressive renal injury afforded by ARB treatment initiated early after five-sixths nephrectomy is associated with normalization of glomerular capillary hydraulic pressure, suppression of proinflammatory gene induction, and macrophage infiltration. 9,10 These data provided support for the hypothesis that after extensive renal mass ablation, expression of ED-1, MCP-1, or ICAM-1 in high numbers of cells in the remnant kidney contributes to progressive renal injury. Although ARB was effective in preventing or attenuating upregulation of several proinflammatory genes in this model, additional interventions that specifically inhibit proinflammatory gene expression may lead to increased therapeutic options for patients with established chronic renal disease progression.…”
Section: Discussionmentioning
confidence: 58%
“…6,7 It was reported recently that clopidogrel has a property of anti-inflammation. CLO may exert its beneficial effects by "cooling off" two important pathogenetic pathways, platelet reactivity and inflammation, both deeply involved in atherothrombotic disease 8,9 ; however, its role in chronic renal injury and the mechanism are unknown. Thus, we hypothesized that combining CLO with irbesartan (IRB), an ARB, may be more effective in attenuating the progression of chronic renal injury through their different actions.…”
mentioning
confidence: 99%